Mystic in the Thread of Everyday Life - Mazzini, María Marcela (Teología, 2018)
In this article I intend to reflect on mystical and everyday life. To do this, first I will briefly define what I mean by mystical; then I will continue with some thoughts about mystic and everyday life in general, taking into account the special relationship which some theologies made by women have with the subject. Finally, I will focus on the thought of Margaret Guenther. I will close these lines with a brief concluding reflection.